PARENTERAL NUTRITION IN PATIENTS IN CRITICAL CONDITIONS: THE HISTORY OF FORMATION AND DEVELOPMENT PROBLEM - Yu. N. Lyashchenko; A. A. Ryk; V. B. Khvatov (Неотложная медицинская помощь)
Parenteral nutrition in patients in critical conditions: the history of formation and development problem.